Safety of video-based telemedicine compared to in-person triage in emergency ophthalmology during COVID-19. (April 2021) - Li, Ji-Peng Olivia; Thomas, Alice A.P.; Kilduff, Caroline L.S.; Logeswaran, Abison; Ramessur, Rishi; Jaselsky, Anton; Sim, Dawn A.; Hay, Gordon R.; Thomas, Peter B.M.
Abstract: Background: the need for social distancing midst the COVID-19 pandemic has forced ophthalmologists to innovate with telemedicine. The novel process of triaging emergency ophthalmology patients via videoconsultations should reduce hospital attendances. However, the safety profile of such services were unknown. Methods: in this retrospective cohort study, we reviewed case notes of 404 adults who used our videoconsultation service from 20/04/2020 to 03/05/2020. We compared these to 451 patient who attended eye casualty in person at the same time who were deemed not to require same day ophthalmic examination. Findings: patients seen by videoconsultations tended to be younger (Median = 43 years, Inter-quartile range = 27 vs Median= 49 years, Inter-quartile range = 28)'. More males used the face-to-face triage (55%) while more females used videoconsultation (54%)%. Fewer patients seen by videoconsultations required specialist review compared to face-face triage [ X 2 (1, N = 854) = 128.02, p <0.001)]. 35.5% of the patients initially seen by videoconsultation had unplanned reattendance within 1 month, compared to 15.7% in the group initially seen in person. X 2 (1, N = 234) = 7.31, p = 0.007). The rate of actual harm was no different (at 0% for each method), with perfect inter-grader correlation when graded independently by two senior ophthalmologists. 97% of patients seen on the video platform surveyed were satisfied with their care. Interpretation: we demonstrate comparable patient safety of videoconsultations at one-month follow-up to in person review. The service is acceptable to patients and reduces the risk of COVID-19 transmission. We propose that videoconsultations are effective and desirable as a tool for triage in ophthalmology. Funding: the research supported by the National Institute for Health Research (NIHR) Biomedical Research Centre based at Moorfields Eye Hospital NHS Foundation Trust and UCL Institute of Ophthalmology who fund PT and DS's time to conduct research. The views expressed are those of the author(s) and not necessarily those of the NHS, the NIHR or the Department of Health.